Calculating the settling velocity of cohesive sediment based on semi-empirical method - Le Nguyen, Hoa Tien; Vo, Luong Hong Phuoc (Vietnam Journal of Marine Science and Technology, 2022)
Settling velocity is an important parameter affecting the characteristics of sediment transport. Especially for cohesive sediment in estuarine or mangrove areas, determination of settling velocity is extremely complex. The study focuses on anlalyzing the relationship between settling velocity and sediment concentration. Based on the empirical formulas of Hwang (1989) and experimental data of Mehta and Li (2003), the settling velocity by concentration is considered with variation of four parameters a, b, m and n. The method is applied to calculate the settling velocity of cohesive sediment in Can Gio Biosphere Reserve, Ho Chi Minh city. From collected sediment samples in fieldwork, the settling column test is used to determine settling velocities. With 38 data of experimental settling velocity, the semi-empirical curve is determined. The results show that the settling velocity in free settling is about 0.28 × 10-5 m/s; the maximum velocity is about 0.99 × 10-3 m/s corresponding to the maximum concentration of 4.7 kg/m3. The resulting values of a, b, m and n are 0.05; 3.5; 3 and 3.2, respectively. The results are reliable to real applications.